Against sexual harassment in workplace as seen in Bombshell movie (2019) (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This article aims to empower woman to fight sexual harassment in workplace as seen in how characters of the film find out what steps were taken in the Bombshell movie (2019) in fighting sexual harassment by Roger Ailes, the CEO of FOX News that based on actual event that happened on 2006. To reach the aim of the study, the author uses qualitative method, and uses the liberal feminism theory of Tong (2009). The data sources were taken from the movie itself and several previous article that have been published between 2011 - 2021 which have been selected according to the topic discussed. The results of this research are, there are several ways shown by some of the characters from this film in fighting sexual harassment, in physical resistance, Gretchen shows it by the way she dares to report the lewd acts committed by Roger Ailes to the authorities. Meanwhile, the fight against verbal sexual harassment is shown by Megyn Kelly's character who firmly opposes the oppression of women which done by Trump, when he is present on her talk show, and the second is shown through Megyn Kelly's dexterity in motivating victims to get up and speak up about Roger Ailes' bad habits.